SISTEM INFORMASI AKUNTANSI PENJUALAN TUNAI PADA PT SARAH CELL SULAWESI - Akram, Al; Salam, Abdul; Hasan, Asriani (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
This study aims to analyze the implementation of cash sales accounting information systems and the effectiveness of internal control at PT Sarah Cell Sulawesi. This study is useful as a reference in strengthening efficient, accountable, and integrated technology-based accounting information systems. The method used is a descriptive qualitative approach with data collection techniques through in-depth interviews with 4 (four) key informants, namely financial managers, sales admins, cashiers, and IT staff. The results of the study indicate that the Zahir Online and Bavaraja application-based information systems have been implemented effectively, allowing recording of sales transactions in real time, automatically, and well documented. This system is integrated with hardware, local and cloud networks, and standard operating procedures. In addition, internal control is strengthened through separation of duties, data verification, and monitoring of daily sales reports that support transparency and accountability. The implications of these findings indicate that the use of appropriate accounting information systems can improve operational efficiency and prevent errors or fraud in the cash sales process. The contribution of this study is to provide a practical overview of the importance of integration between technology. HR, and procedures in effective sales management in the digital era.